(3GdeSGFd (B( (3aj Yde CMcGe GdfLhe(B)s - (3CHh jhSa jYbhH Hf Ydj GdbQTj GdbUQGfj, GdbUQGfj,J (B200 (3g` s ((3GdbSWfWjfjI s)
(3BNQgG (B:s
(3aEfg jNW efRdg Ohf efRdg HEPf Gddg JYGdi s
(3ajgG HYV GdQShe GdgfOSjI hGdLOGhds
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B122s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B392 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B97 s
Keywords: (3Gdadcs